The Histidine-Rich Calcium Binding Protein in Regulation of Cardiac Rhythmicity - Arvanitis, Demetrios A.; Vafiadaki, Elizabeth; Johnson, Daniel M.; Kranias, Evangelia G.; Sanoudou, Despina (Frontiers in Physiology, 2018)
Sudden unexpected cardiac death (SCD) accounts for up to half of all-cause mortality of heart failure patients. Standardized cardiology tools such as electrocardiography, cardiac imaging, electrophysiological and serum biomarkers cannot accurately predict which patients are at risk of life-threatening arrhythmic episodes. Recently, a common variant of the histidine-rich calcium binding protein (HRC), the Ser96Ala, was identified as a potent biomarker of malignant arrhythmia triggering in these patients. HRC has been shown to be involved in the regulation of cardiac sarcoplasmic reticulum (SR) Ca2+ cycling, by binding and storing Ca2+ in the SR, as well as interacting with the SR Ca2+ uptake and release complexes. The underlying mechanisms, elucidated by studies at the molecular, biochemical, cellular and intact animal levels, indicate that transversion of Ser96 to Ala results in abolishment of an HRC phosphorylation site by Fam20C kinase and dysregulation of SR Ca2+ cycling. This is mediated through aberrant SR Ca2+ release by the ryanodine receptor (RyR2) quaternary complex, due to the impaired HRC/triadin interaction, and depressed SR Ca2+ uptake by the sarco/endoplasmic reticulum Ca2+ ATPase (SERCA2) pump, due to the impaired HRC/SERCA2 interaction. Pharmacological intervention with KN-93, an inhibitor of Ca2+/calmodulin-dependent protein kinase II (CaMKII), in the HRC Ser96Ala mouse model, reduced the occurrence of malignant cardiac arrhythmias. Herein, we summarize the current evidence on the pivotal role of HRC in the regulation of cardiac rhythmicity and the importance of HRC Ser96Ala as a genetic modifier for arrhythmias in the setting of heart failure.